Second European Quality of Life Survey: Evaluating the quality of society and public services - Rose, Richard; Newton, Kenneth (Luxembourg, 2010)
"Public services are the bedrock of modern society. They impact on people’s everyday lives to a greater or lesser degree: from education and health services to public transport, refuse collection and state pensions. This report explores the interaction between individuals and institutions, analysing to what extent the key social services are responsible for shaping the quality of people’s lives. Drawing on findings from the second European Quality of Life Survey, carried out by Eurofound in 2007 across 28 countries in Europe, the report gives a wideranging picture of the diverse social realities in Europe today. It assesses the multiple influences at work in society – such as access to health services, quality of local environment, racial and ethnic mix, as well as police, legal and political bodies – in the light of individual income, gender and age."